Evaluating the Validity and Effectiveness of Multiantro Tools in Diverse Applications - Arga, Muhammad Wahyu; Sukamti, Endang Rini; Srianto, Widha; Wahyuti, Sri Ayu; Pamungkas, Okky Indera; Budiarti, Ratna; Nurfadhila, Risti; Prasetyo, Heru (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
Anthropometry is a science created from a new scientific sub-discipline called physical anthropology which is an implication of the development of anthropological studies. Anthropometry plays a very important role in the world of sports. An ideal anthropometric composition and supported by good technique will produce an athlete's excellent performance in the competition. Anthropometric characteristics, body composition and mass contribute to training and competition performance. Therefore, researchers have developed a multifunctional anthropometric measurement tool, several test items can be carried out simultaneously with the use of this tool, this tool is called 'Multiantro